Comparing Particle Emission Scenarios in Hydrodynamics: Continuous Emission vs. Freeze-out - Grassi, F.; Hama, Y.; Kodama, T.; Socolowski, O. [UNESP] (My University, 1997)
The usual particle emission scenario used in hydrodynamics presupposes that particles instantaneously stop interacting (freeze-out) once they reach some three dimensional surface. Another formalism has been developed recently where particle emission occurs continuously during the whole expansion of thermalized matter. Here we compare both mechanisms in a simplified hydrodynamical framework and show that they lead to a drastically different interpretation of data.